Unity and Language A Study in the Philosophy of Johann Georg Hamann - O'Flaherty, James C. (UNC Studies in the Germanic Languages and Literatures, 1952)
This 1952 study is an investigation into the nature of language that focuses on reinterpreting Hamann's theories of language in light of twentieth century linguistic philosophy. One of the first studies of Hamann to be presented in English, it poses many questions of universal concern and interest.